A Frameless 2-Coloring of the Plane Lattice. Issue 5 (7th December 2021) - Kaplan, Craig S.; Shallit, Jeffrey
Summary: A picture frame in two dimensions is a rectangular array of symbols, with at least two rows and columns, where the first and last rows are identical, and the first and last columns are identical. If a coloring of the plane lattice has no picture frames, we call it frameless . In this note, we show how to create a simple 2-coloring of the plane lattice that is frameless.